High–rate electrochemical capacitors from highly graphitic carbon–tipped manganese oxide/mesoporous carbon/manganese oxide hybrid nanowires - Jiang, Hao (2011)
In this paper, using manganese oxide as an example, we report the successful design and synthesis of